Understanding how junction resistances impact the conduction mechanism in nano-networks - Gabbett, Cian (2024)
Funding Information: We acknowledge funding from the European Union through the ERC grant FUTUREPRINT, the Graphene Flagship and the Horizon Europe project 2D-PRINTABLE (GA-101135196). We have also received support from the Science Foundation Ireland (SFI) funded centre AMBER (SFI/12/ RC/2278_P2) and availed of the facilities of the SFI-funded advanced microscopy laboratory (AML), additive research laboratory (ARL) and iCRAG. A.G.K. acknowledges funding from the Marie Skłodowska-Curie Postdoctoral Fellowship “NanoHarvest” (Proposal Number: 101107032). T.C. acknowledges funding from a Marie Skłodowska-Curie Individual Fellowship “MOVE” (grant number 101030735, project number 211395, and award number 16883). L.D appreciates support from Science Foundation Ireland (SFI) (18/EPSRC-CDT/3581). E.Ca appreciates support from the Irish Research Council (IRC) (GOIPG/2020/1051). J.M. acknowledges his Margarita Salas fellowship from the Spanish Ministry of Universities. A.M. acknowledges support from the European Research Council Starting Grant POL_2D_PHYSICS (101075821) and the Austrian Science Fund Y1298-N START Prize. NY is funded by the SFI US-Ireland project (21/US/3788). G.G., S.K. and L.D.A.S. received funding from the Netherlands Organisation for Scientific Research (NWO) in the frame- work of the Materials for sustainability and from the Ministry of Economic Affairs in the framework of the PPP allowance. Z.S. was supported by ERC-CZ program (project LL2101) from Ministry of Education Youth and Sports (MEYS) and acknowledges laser infrastructure from project reg. No. CZ.02.1.01/0.0/0.0/15_003/0000444 financed by the EFRR. We thank Prof. Matthias Moebius for useful discussions. Publisher Copyright: © The Author(s) 2024.